Quality indicators for the design and construction of MOOC courses - Fernández-Cerero, José; Cabero-Almenara, Julio; Fernández-Batanero, Jose María (IJERI: International Journal of Educational Research and Innovation, 2024)
The purpose of this study is to validate a data collection instrument that not only allows the evaluation of a MOOC, but also incorporates essential criteria for the design and development of online courses of this type. An analysis was carried out to determine the content validity and reliability of the instrument. For content validation, the "Expert Judgment" technique was employed, using a method for the selection of experts known as the "Expert Competence Coefficient" or "K-Coefficient". The reliability of the instrument was calculated using two measures: Cronbach’s alpha and McDonald’s Omega. The results confirmed that the questionnaire studied is a valid and reliable instrument for identifying critical sub-dimensions that facilitate the design and creation of quality-assured courses of this nature. Furthermore, the study underlines the importance of the Expert Competence Coefficient (ECC) as a key element for a more accurate and soundly based expert selection.